Study of the morphology and structure of hybrid biodegradable 3d scaffolds based on piezoelectric Poly(l-lactic acid) and rGO/GO for bone tissue engineering; Перспективные материалы конструкционного и функционального назначения - Jekhan A. M. S.; Chernozem R. V. Roman Viktorovich; Mukhortova Yu. R. Yulia Ruslanovna; Surmeneva M. A. Maria Alexandrovna; Skirtach A. G.; Surmenev R. A. Roman Anatolievich (Функциональные материалы, 2020)
Заглавие с экрана